When Illusion Met Illusion: How Interacting Biases Affect (Dis)trust within Coopetitive Policy Networks. (6th April 2021) - Lee, Junesoo
Abstract: Coopetition is a universal relationship in policy networks where various organizations cooperate and also compete with one another. Dealing with the ambivalent relationships in policy networks, organizations in the network need to assess their internal and external environments. However, such assessments are usually inclined to be biased for various reasons. The question is "If multiple organizations' assessment biases interact with one another, what happens to mutual trust or distrust?" This study explores the patterns and impact of interactions of assessment biases using surveys and interviews administered to nuclear‐related public institutions in South Korea. The findings imply that the interactions of individual biases impact trust and distrust differently according to diverse dimensions of bias, including power, cooperation, competition, and contribution in policy networks. What determines trust or distrust among network members may not only be whether biases exist but also how biases of network members are combined and matched.